Navigating AI for cohesion: A Qualitative analysis of preparatory paragraphs in an ELT context - Agustien, Najwa Septya; Fanany, Syarla Salsabilla; Maisa, Maisa; Wirabhakti, Agus; Kereibayeva, Aigerim (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
Despite the proliferation of research on educational technology, a scarcity of studies has systematically examined the development of technology skills for employing AI-generated cohesion devices, particularly in the preparatory paragraphs of academic writing within English Language Teaching (ELT). Addressing this gap, this study adopted a qualitative descriptive approach, incorporating thematic and textual analysis. Data were drawn from the introductory paragraphs of final project essays authored by undergraduate students in an English Department during the 2020-2021 academic year. Analysis revealed a total of 183 cohesive devices. The predominant type was collocation (54.87%), followed by repetition (23.10%), reference (11.19%), and conjunction (10.83%). Furthermore, while students were found to utilize AI-supported writing tools—including ChatGPT, Grammarly, QuillBot, and DeepL—their engagement was largely confined to a limited range of prominent platforms, suggesting underutilization of the broader ecosystem of AI writing technologies. Student interaction with these tools was often unintentional, yet it did not preclude the active application of critical thinking. Key indicators of this critical engagement included Brainstorming, Structured Questioning, Idea Selection, and Strategic Choice, which delineate the process by which students adapt AI-generated suggestions. This adaptive process aligns with the Sustainable Development Goal (SDG) of Quality Education by fostering inclusive and equitable access to digital literacy and higher-order thinking skills. The study contributes to the fields of Educational Technology and Digital Pedagogy by elucidating how AI tools can be harnessed to support critical and creative thinking within academic writing instruction.